Safety and tolerability of pirfenidone in asbestosis: a prospective multicenter study - Jelle R. Miedema; Catharina C. Moor; Marcel Veltkamp; Sara Baart; Natascha S. L. Lie; Jan C. Grutters; Marlies S. Wijsenbeek; Rémy L. M. Mostard (Respiratory Research, 2022)
Abstract Background Pirfenidone slows down disease progression in idiopathic pulmonary fibrosis (IPF). Recent studies suggest a treatment effect in progressive pulmonary fibrosis other than IPF. However, the safety and effectiveness of pirfenidone in asbestosis patients remain unclear. In this study, we aimed to investigate the safety, tolerability and efficacy of pirfenidone in asbestosis patients with a progressive phenotype. Methods This was a multicenter prospective study in asbestosis patients with progressive lung function decline. After a 12-week observational period, patients were treated with pirfenidone 801 mg three times a day. Symptoms and adverse events were evaluated weekly and patients completed online patient-reported outcomes measures. At baseline, start of therapy, 12 and 24 weeks, in hospital measurement of lung function and a 6 min walking test were performed. Additionally, patients performed daily home spirometry measurements. Results In total, 10 patients were included of whom 6 patients (66.7%) experienced any adverse events during the study period. Most frequently reported adverse events were fatigue, rash, anorexia and cough, which mostly occurred intermittently and were reported as not very bothersome. No significant changes in hospital pulmonary function (forced vital capacity (FVC), diffusion capacity of the lung for carbon monoxide (DLCO), 6 min walking test or patient-reported outcomes measures before and after start of pirfenidone were found. Home spirometry demonstrated a FVC decline in 12 weeks before start of pirfenidone, while FVC did not decline during the 24 week treatment phase, but this difference was not statistically significant. Conclusions Treatment with pirfenidone in asbestosis has an acceptable safety and tolerability profile and home spirometry data suggest this antifibrotic treatment might attenuate FVC decline in progressive asbestosis. Trial registration MEC-2018-1392; EudraCT number: 2018-001781-41